Altered Immune Phenotypes and HLA-DQB1 Gene Variation in Multiple Sclerosis Patients Failing Interferon β Treatment - Devi-Marulkar, Priyanka; Moraes-Cabe, Carolina; Campagne, Pascal; Corre, Béatrice; Meghraoui-Kheddar, Aida; Bondet, Vincent; Llibre, Alba; Duffy, Darragh; Maillart, Elisabeth; Papeix, Caroline; Pellegrini, Sandra; Michel, Frédérique (Frontiers in Immunology, 2021)
Background: Interferon beta (IFNβ) has been prescribed as a first-line disease-modifying therapy for relapsing-remitting multiple sclerosis (RRMS) for nearly three decades. However, there is still a lack of treatment response markers that correlate with the clinical outcome of patients. Aim: To determine a combination of cellular and molecular blood signatures associated with the efficacy of IFNβ treatment, using an integrated approach. Methods: The immune status of 40 RRMS patients, 15 of whom were untreated and 25 that received IFNβ1a treatment (15 responders, 10 non-responders), was investigated by phenotyping regulatory CD4+ T cells and naïve/memory T cell subsets, by measurement of circulating IFN/β proteins with digital ELISA (Simoa) and analysis of  600 immune related genes including 159 interferon-stimulated genes (ISGs) with the Nanostring technology. The potential impact of HLA class II gene variation in treatment responsiveness was investigated by genotyping HLA-DRB1, -DRB3,4,5, -DQA1 and -DQB1, using as a control population the Milieu Interieur cohort of 1000 French healthy donors. Results: Clinical responders and non-responders displayed similar plasma levels of IFN and similar ISG profiles. However, non-responders mainly differed from other subject groups with reduced circulating naïve regulatory T cells, enhanced terminally differentiated effector memory CD4+ TEMRA cells, and altered expression of at least six genes with immunoregulatory function. Moreover, non-responders were enriched for HLA-DQB1 genotypes encoding DQ8 and DQ2 serotypes. Interestingly, these two serotypes are associated with type 1 diabetes and celiac disease. Overall, the immune signatures of non-responders suggest an active disease that is resistant to therapeutic IFN, and in which CD4+ T cells, likely restricted by DQ8 and/or DQ2, exert enhanced autoreactive and bystander inflammatory activities.